PRÉSTAMOS CAROS A LAS PYMES; LE RESTAN COMPETITIVIDAD - Mauricio Pachas, Pablo Willins (2004)
The objective of this study is to show thai the excessive interest rates over 100% per annun of the loans to SMB detracts their competiveness and deteriorates their capital. Similar/y, to propase new [inancial mechanisms and alternatives to the traditional system because more than 82% of the SMB can' t have access to the Multiple Commercial Banks which offer loans with lesser interest raies, with an average of 20% per annun (Local Currency Annual Interest Rate-LCAIR). By the study and exploration methodology of secondary sources, the main problem of the SMB is highlightedas tfiefinancia/ one, as told by 65% of them. Results revea[ that the interest rates that charge the small financial institutions Cmicrcfinancieras") is in the arder of 98.7% per annun (Edpyme-SMB development institutions), 135.98% the (Caja Municipal-Local Municipalities Loans Institutions) and 186.8% the Consumer Banks, which are excessive when compared to the average 20% charged by the Multiple Banks and it has been found that 50% of thefinancing to the sharks which charge an interest rate of more than 10% per month which roughly represents an interest rate of 213.84% per annun, in absence of an effective Government Policy Act in support oftheSMB. Conclusions: The most expensive loans of the Peruvian financial system are the ones that are given to the SMB. This is aggravated by the high level of informality of the industry, which is in the arder of the 60%, which is similar to the informality of the Peruvian economy in the arder of the 59.4% of the DGP (Domestic Cross Product). It is then imperative to revert its troublesome state and in this sense, our proposal represents and alternative to the traditional financial system by considering converting the government owned Financial Development Corporation (COFIDE in Spanish) (using its underutilized capacity) into a SMB Bank and thus gaining access to international credit lines at international credit rates and lending then to the SMB at market interest rates.